2009
DOI: 10.1080/09638280801983486
|View full text |Cite
|
Sign up to set email alerts
|

Identification of quasi-in-need-of-care state (QUINOCS) among community dwelling elderly people using a seven-item subset of the Functional Independence Measure (FIM™)

Abstract: The screening method using the 7-item subset of the FIM can be used for identification of the QUINOCS among elderly people efficiently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The motor FIM was shown to be valid, reliable and able to detect changes in disability [ 19 ] and was successfully used in a recent study dealing with patients after hip fracture [ 20 ]. Previously, some studies used only parts of the FIM in community dwelling elderly people [ 21 ], for use in long-term care setting [ 22 ], or spinal cord injuries [ 23 ] and described their score as valid [ 22 ], sensitive and specific [ 21 ], and reliable [ 23 ]. Our physiotherapists had been well trained in evaluating mobility using the FIM in advance.…”
Section: Methodsmentioning
confidence: 99%
“…The motor FIM was shown to be valid, reliable and able to detect changes in disability [ 19 ] and was successfully used in a recent study dealing with patients after hip fracture [ 20 ]. Previously, some studies used only parts of the FIM in community dwelling elderly people [ 21 ], for use in long-term care setting [ 22 ], or spinal cord injuries [ 23 ] and described their score as valid [ 22 ], sensitive and specific [ 21 ], and reliable [ 23 ]. Our physiotherapists had been well trained in evaluating mobility using the FIM in advance.…”
Section: Methodsmentioning
confidence: 99%
“…However, Rasch analysis has revealed that the BI has no psychometric properties that enable the measurement of patients' ability 3) . In Japan, several evaluation instruments have been developed for caregivers to assess patients' ADL ability at home, such as the questionnaire version of the FIM 4) , the short version of the FIM 1,5) , the computer program to assist evaluating the FIM 6) , and the University of Occupational and Environmental Health self-assessment version of the BI 7) . The reliability and validity of these instruments have been examined.…”
Section: Introductionmentioning
confidence: 99%
“…To simplify the FIM evaluation, the short version of the FIM excludes cognitive items whose reliability is inferior to motor items, and consequently contains only seven motor items. The short version of the FIM involves a complex scoring process and requires expert knowledge to administer, so is not suitable for home use 1,5) . The FIM questionnaire, a computer program to assist evaluating the FIM, and the University of Occupational and Environmental Health self-assessment version of the BI have not yet been examined using Rasch analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although generally used in either acute or post-acute rehabilitation facilities, the FIM can be modified for use as a measurement instrument for community-dwelling elderly people (Yamada, Liu, Fujimoto, Hase, Tsuji, Fujiwara & Okajima, 2009). In a study done in Japan, a modified version of the FIM using seven subset activities from the original thirteen motor items yielded high correlations to the original 13-item motor FIM scores, and was able to predict which individuals in the study could benefit from rehabilitation and intervention (Yamada, et al, 2009).…”
Section: Functional Assessments For Older Adultsmentioning
confidence: 99%